Anticipate, Absorb, Reshape (A2R): A Baseline Study of Climate Resilience in Developing Countries - Dale, Lisa; Held, Jonathan; Ratte, Stephanie; Zaman, Farrukh (Consilience, 2018)
The United Nations Climate Resilience Initiative: Anticipate, Absorb, Reshape (A2R) is a global, UN-led, multi-stakeholder initiative that strengthens climate resilience for vulnerable countries and people. A2R addresses the urgent needs of Least Developed Countries (LDCs), Small Island Developing States (SIDS), Africa and other vulnerable regions. The initiative accelerates action on key aspects of climate resilience under its three pillars: 1) Anticipate – Increased capacity to better anticipate and act on climate hazards and stresses through early warning and early action; 2) Absorb – Increased capacity to absorb shocks by increasing access to climate risk insurance and social protection systems; and 3) Reshape – Increased capacity to reshape development pathways by transforming economies to reduce risks and root causes of vulnerabilities and support the sound management of physical infrastructure and ecosystems to foster climate resilience. This report outlines the current status of key indicators relevant to the three pillars. It also identifies some of the challenges faced in this analysis and suggests ways of overcoming them, so that we may, in the future, be able to provide a fuller picture of progress on these three key capacities for climate resilience.